2015
DOI: 10.3390/ijerph120303215
|View full text |Cite
|
Sign up to set email alerts
|

The Components of Self-Perceived Health in the Kailali District of Nepal: A Cross-Sectional Survey

Abstract: Self-perceived health is a health measure with well-established links with mortality, healthcare services utilization, and future health. Various components of self-perceived health have been identified in different populations. In this study, we aimed to investigate the components of self-perceived health in a Nepali population. This was a cross-sectional survey conducted in the Kailali district of Nepal in 2014. The sample was initially consisted of 309 households, representative of the population of one mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
1
20
0
6
Order By: Relevance
“…Self-rated health is an increasingly used indicator in epidemiological studies due to its validity and reliability, strongly associating the real health state and health goal by incorporating physical, cognitive and emotional aspects 7,8 . It is an easily obtained variable that offers valuable information regarding the studied population as it is influenced not only by the presence of diseases but by well-being, life satisfaction, functional capacity and quality of life [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Self-rated health is an increasingly used indicator in epidemiological studies due to its validity and reliability, strongly associating the real health state and health goal by incorporating physical, cognitive and emotional aspects 7,8 . It is an easily obtained variable that offers valuable information regarding the studied population as it is influenced not only by the presence of diseases but by well-being, life satisfaction, functional capacity and quality of life [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The finding is consistent with previous finding that shows being a nonsmoker was associated with more positive SRH levels across the adult life course 11 . Another study conducted in Kailali district also found that non-smoking status and higher level of happiness were associated with better selfperceived health 12 . It indicates that unhealthy behavior like smoking might be associated with morbidities that cause poor perceived health status.…”
Section: Discussionmentioning
confidence: 88%
“…Identifying factors associated with SRH in a specific context has public health implication because it helps to better address specific characteristics of the population through public health policies and more targeted interventions. Several socio-demographic, socioeconomic, health behaviors, health condition and psychosocial factors are found to be associated with self-perceived health in different populations 6,[10][11][12] . After controlling for age, sex and region, all socio-demographic factors were related to SRH 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), is viewed with scepticism as the respondents may fail to perceive illness or health deficits because of lack of awareness. 33 However, Cullati S et al in their construct validity study of SRH reliability in India concluded that the single SRH item is a reliable indicator of general health in the population of India. 34 Moreover, Falk H et al, supported the use of SRH as a simple measure in survey settings to identify vulnerable groups and evaluate targeted health interventions in resource-scares settings.…”
Section: Discussionmentioning
confidence: 99%